Ability of Pediatric Emergency Medicine Physicians to Identify Anatomic Landmarks With the Assistance of Ultrasound Prior to Lumbar Puncture in a Simulated Obese Model. Issue 1 (January 2015) - Restrepo, Christopher G.; Baker, Mark D.; Pruitt, Christopher M.; Gullett, John P.; Pigott, David C.
<x xml:space="preserve">Abstract</x> Objectives Lumbar punctures (LPs) are typically performed using anatomical surface landmarks. However, as body mass index increases, identifying surface landmarks becomes more difficult. Ultrasound has been proposed as a tool for identifying these landmarks prior to LP. This study evaluates the effectiveness of a brief training program in ultrasound identification of anatomical landmarks in a simulated obese model prior to completing an LP. Methods Pediatric emergency medicine physicians completed a pretest questionnaire on ultrasound familiarity prior to an educational session. Participants utilized ultrasonography without the assistance of palpation on a simulation LP model saving images for review. Participants attempted LP on phantom models with simulated body mass indices of 35 and 40 kg/m2. Time to image acquisition and successful aspiration of cerebrospinal fluid from the model were recorded. Two expert sonologists independently reviewed all images for correct landmark identification. Results Seven of the 19 participants had previous familiarity with ultrasound. The mean time to lumbar image acquisition significantly improved for all individuals from 176 seconds to 100 seconds (P = 0.003). Comfort level with ultrasound improved (P < 0.001) as well as comfort level in performing a lumbar ultrasound (P < 0.001). Adequate images were obtained in 96% of the attempts (55/57). The success rate at performing LP was 95% (54/57). Conclusions After a brief education intervention, pediatric emergency medicine physicians with little to no previous training in ultrasound can obtain adequate lumbar anatomic images and successfully perform LP in a simulated obese model. Comfort level with ultrasound significantly improves with a short course in ultrasound fundamentals.